Empoderamiento y roles de género: experiencias de mujeres líderes de turismo comunitario en Perú - Sánchez Florez, Lucia (2022)
Tourism has great potential as a driver of social change and to reduce gender gaps. This research aims to analyze the situation of empowerment and gender roles of women leaders of four experiences of community tourism in Peru. The methodology is based on qualitative approach, the research is descriptive and transversal, and the method is study of cases. We collected information from four women leaders in community-based tourism enterprises in the north, center and south of Peru. Two techniques were used to collect this information: the in-depth interview and the discussion group. Qualitative data analysis was performed using the ATLAS.ti program. The results show how women have been empowered in personal, economic and political spheres despite the patriarchal resistance of their communities. On a personal level, leadership, self-esteem and critical awareness have been improved. At political level, collective agency, social capital and participation stand out. At economic level, there is evidence of less empowerment. Regarding gender roles, although women assume more domestic tasks, they currently also carry out productive, reproductive and community roles. This triple role is played by women in unequal conditions to men. The factors that have promoted this empowerment and change of gender roles are: strengthening of capacities; intercultural relationship with tourists; exchange of experiences between women and community organizations; institutional support and the strong will, capacity for agency and personal and collective determination of women. Although the results are not decisive and respond to situated contexts, it is concluded that a trend towards greater empowerment of women and a greater presence in decision-making spaces exists, reconfiguring gender mandates and the sexual division of labor, all through the development of community tourism.